Pengaruh Penggunaan Media LooseParts Terhadap Kemampuan Pra Membaca Anak Usia 4-5 Tahun Di RA Miftahul Khoir Pandeglang Banten - Nadiatus sa’diah; Uyu Mu’awwanah; Muhiyatul Huliyah (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to determine the effect of implementing loose parts–based learning media on improving pre-reading skills in children aged 4–5 years. The research employed a quasi-experimental method with a control group pre-test–post-test design. The sample consisted of all students in classes B1 and B2, totaling 30 children. The study was conducted in four sessions: the first for the pre-test, the second and third for the treatment, and the final session for the post-test. The research instrument was a pre-reading skills test consisting of 20 validated items. The results showed that the experimental class, which received learning activities using loose parts media, achieved an average score of 71.96 or 72 percent, categorized as effective. In contrast, the control class, which received conventional learning without treatment, obtained an average score of 32 or 32 percent, categorized as ineffective. Hypothesis testing using the non-parametric Mann–Whitney test yielded a Z value of −4.071 with a significance level of 0.00, which is less than 0.05. Therefore, Ha was accepted and Ho was rejected, indicating that the use of loose parts media has a significant effect on the pre-reading skills of children aged 4–5 years.